Experimental study on the characteristics of air–water two-phase flow in vertical helical rectangular channel. (July 2015) - Liu, X.F.; Xia, G.D.; Yang, G.
Highlights: Flow pattern and flow patterns evolution in vertical helical rectangular channel. Flow pattern map and flow pattern transition in vertical helical rectangular channel. The local parameters of slug flow in different positions. Measurements of the liquid film thickness under the different superficial liquid velocity. Abstract: Experimental investigations on the characteristics of air–water two-phase flow in the vertical helical rectangular channel are performed using the high speed flow visualization. The flow pattern map and the transition in the helical rectangular channel are presented. The flow pattern evolution in different positions of the helical rectangular channel is illustrated. The discussion on the coalescence of the bubble and slug is presented. The slug velocity, slug length distribution, liquid slug frequency, falling liquid film velocity and falling film thickness along the slug are investigated. The dimensionless liquid film thickness of the annular flow on the outer side of the channel is measured using the digital image processing algorithm.